Factors affecting the implementation of the corporate strategy of the Mpumalanga Department of Education : an analytical approach - Baloyi, Albert Hlengani (My University, 2010)
Refer to document
Thesis (MBA) -- University of Limpopo, 2010
Keywords: Strategic planning; Strategic goals; Strategic planning -- South Africa -- Mpumalanga; Corporate planning -- South Africa -- Mpumalanga; Organisational effectiveness